Meta-Analysis of Oral Anticoagulants and Adverse Outcomes in Atrial Fibrillation Patients After Intracranial Hemorrhage - Liu, Xin; Guo, Siyu; Xu, Zhicheng (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND: Intracranial hemorrhage (ICH) was excluded in most anticoagulation randomized clinical trials (RCTs), so oral anticoagulant (OAC) therapy is still conventional for atrial fibrillation (AF) patients after ICH. Therefore, we conducted a meta-analysis to determine the effectiveness and safety outcomes of OAC for these patients. METHODS: We systematically searched the PubMed and Embase databases up to March 2022 for RCTs and observational studies, exploring the effect of OAC in AF patients after ICH. The effectiveness outcomes included stroke or systemic embolism, ischemic stroke, and all-cause death, whereas the safety outcomes were major bleeding and recurrent ICH. Hazard ratios (HRs) and 95% confidence intervals (CIs) from each study were pooled using a random-effects model. RESULTS: 14 studies were totally included. OAC therapy performed reduced risks of stroke or systemic embolism (HR=0.65, 95% CI 0.53-0.81), ischemic stroke (HR=0.70, 95% CI 0.60-0.82), and all-cause death (HR=0.43, 95% CI 0.27-0.70), but higher risk of major bleeding (HR=1.50, 95% CI 0.94-2.40), no difference in recurrent ICH (HR=0.91, 95% CI 0.53-1.55) versus no OAC therapy. Among non-vitamin K antagonist oral anticoagulant (NOAC) therapy, lower risk of stroke or systemic embolism (HR=0.83, 95% CI 0.70-0.98), all-cause death (HR=0.67, 95% CI 0.53-0.84), and recurrent ICH (HR=0.68, 95% CI 0.54-0.86) were found versus vitamin K antagonists (VKA) therapy. CONCLUSIONS: OAC therapy (especially VKA) revealed superior effectiveness in AF patients after ICH, and the superiority of NOAC was also found, but some related evidence was limited.